EFFECT OF SUCROSE AND NUTRIENT ELEMENTS ON FRUITING QUALITY OF KESAR MANGO - S. D. , JARANDE; B. N. , PATEL; AND G. S. TEKALE, S. S. MINGIRE (The Bioscan, 2016)
A study was carried out to evaluate the effect of sucrose and nutrient elements on fruit quality characteristics of Kesar mango. It was performed during season 2009-2010 at Agriculture Experimental Station, Navsari Agricultural University, Paria, Ta- Pardi and Dist- Valsad. The present experiment was laid out in Randomized Block Design (RBD) with ten treatments and replicated thrice. The treatments are integrated effect of nutrients on trees was found significant on value of TSS (19.00 0 Brix) and ascorbic acid (72.89 mg/100g pulp) content of fruits was noted in treatment T8- sucrose 10% + boric acid 0.5%., it was followed by treatment T5- sucrose 5% + boric acid 0.5%., Other quality parameters like reducing sugar, total sugar, acidity, non-reducing sugar etc. were not affected by different treatments.